Trichloroacetic Acid Ingestion: Self-Harm Attempt - Black, E. R. (Case Reports in Psychiatry, 2017)
Objective. Trichloroacetic acid (TCAA), or trichloroethanoic acid, is a chemical analogue of acetic acid where three methyl group hydrogen atoms are replaced by chlorine. TCAAs are also abbreviated and referred to as TCAs, causing confusion with the psychiatric antidepressant drug class, especially among patients. TCAAs exist in dermatological treatments such as chemical peels or wart chemoablation medication. TCAA ingestion or overdose can cause gastric irritation symptoms including vomiting, diarrhea, or lassitude. This symptomatology is less severe than TCA overdose, where symptoms may include elevated body temperature, blurred vision, dilated pupils, sleepiness, confusion, seizures, rapid heart rate, and cardiac arrest. Owing to the vast difference in symptoms, the need for clinical intervention differs greatly. While overdose of either in a self-harm attempt can warrant psychiatric hospital admission, the risk of death in TCAA ingestion is far less. Case Report. A patient ingested TCAA in the form of a commercially available dermatological chemical peel as a self-harm attempt, thinking that it was a more injurious TCA. Conclusion. Awareness among physicians, particularly psychiatrists, regarding this relatively obscure chemical compound (TCAA) and its use by suicidal patients mistakenly believing it to be a substance that can be significantly more lethal (TCA), is imperative.